Analysis of rheological properties of Halvasan as function of ingredients using response surface methodology - Patel, Amitkumar Manojbhai; Modha, Hiralkumar M.; Dharaiya, Chetan N.; Patel, Dhinalkumar H.; Patel, Hasmukhbhai G. (Indian Journal of Dairy Science, 2016)
Rheological properties of Halvasan as a function of ingredients viz. gluten, fada and maida were investigated using five level three factor central composite rotatable design of response surface methodology. Hardness of Halvasan was significantly negatively (P £ 0.05) and significantly positively (P £ 0.01) influenced by gluten and fada, respectively at linear level. At quadratic term, level of fada (P £ 0.05) and maida (P £ 0.01) had significantly negative effect on hardness of Halvasan. Gumminess of Halvasan was significantly positively (P £ 0.01) and significantly negatively (P £ 0.01) influenced by fada and maida, respectively at linear level. At quadratic term, level of gluten (P £ 0.01) and fada (P £ 0.05) had significantly positive effect on gumminess of Halvasan. Adhesiveness of Halvasan was significantly positively influenced by fada (P £ 0.01) and maida (P £ 0.05), respectively at linear level. At quadratic term, level of gluten (P £ 0.01) and maida (P £ 0.05) had significantly negative effect on gumminess of Halvasan. Interaction term of gluten and fada significantly negatively (P £ 0.05) affected hardness while interaction effect of gluten-maida and fada-maida significantly positively (P £ 0.01) affected gumminess of Halvasan. The coefficient of determination values (R2) ranged from 0.817-0.949 for the relevant quadratic regression model.